Condition of Soils in Georgia Caused by Natural and Anthropogenic Factors - Zhorzholiani, Tsira; Gordadze, Emzar; Afkhadze, Ketevan (Bulletin of Akaki Tsereteli State University, 2026)
Soils are the foundation and one of the basic elements of almost every aspect of human activity. They can be used as an essential tool of human habitation, work, production and therefore represent a major resource of revenues and prosperity. For the above enumerated reasons a rational exploitation of soil resources is an indispensable precondition of the mankind’s very existence. The article proposes the analysis of soil conditions in Georgia from the perspective of anthropogenic and natural factors.